2022
DOI: 10.1124/jpet.121.001045
|View full text |Cite
|
Sign up to set email alerts
|

Role of Efficacy as a Determinant of Locomotor Activation by Mu Opioid Receptor Ligands in Female and Male Mice

Abstract: Mu opioid receptor (MOR) agonists produce locomotor hyperactivity in mice as one sign of opioid-induced motor disruption. The goal of this study was to evaluate the degree of MOR efficacy required to produce this hyperactivity. Full dose-effect curves were determined for locomotor activation produced in male and female Institute of Cancer Research (ICR) mice by (1) eight different single-molecule opioids with high to low MOR efficacy and (2) a series of fixed-proportion fentanyl/naltrexone mixtures with high t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 44 publications
7
33
0
Order By: Relevance
“…The present study builds on these previous findings by demonstrating that climbing is highly sensitive to disruption by MOR agonists and has a very low MOR efficacy requirement. Specifically, previous work in our lab has used fixed-proportion fentanyl/naltrexone mixtures as a strategy to quantify the efficacy requirements for a wide range of MOR agonist-induced behavioral endpoints in mice, rats, and rhesus monkeys ( 36 , 38 40 ). Application of this approach in the present study revealed that climbing in mice is the most sensitive behavioral effect we have evaluated in any species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The present study builds on these previous findings by demonstrating that climbing is highly sensitive to disruption by MOR agonists and has a very low MOR efficacy requirement. Specifically, previous work in our lab has used fixed-proportion fentanyl/naltrexone mixtures as a strategy to quantify the efficacy requirements for a wide range of MOR agonist-induced behavioral endpoints in mice, rats, and rhesus monkeys ( 36 , 38 40 ). Application of this approach in the present study revealed that climbing in mice is the most sensitive behavioral effect we have evaluated in any species.…”
Section: Discussionmentioning
confidence: 99%
“…Step 2 evaluated effects produced by a series of fixed-proportion fentanyl/naltrexone mixtures. We have reported previously that the proportion of fentanyl in fentanyl/naltrexone mixtures can be manipulated such that decreasing fentanyl proportions result in decreasing net efficacy of the mixture ( 36 , 38 40 ). Here, we examined 10:1, 3.2:1, and 1:1 mixtures of fentanyl/naltrexone.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This opioidinduced hyperlocomotion is dependent on dopaminergic activation [31][32][33] , namely the activation of MORs expressed on GABA afferents onto VTAdopamine neurons 34 . Additionally, locomotor activation can distinguish between full and partial MOR agonists, with partial agonists producing graded increases dependent on e cacy 35 . We found that (R,S)-MTD and (R)-MTD increased locomotion, but (S)-MTD did not (Fig.…”
Section: Divergent Pharmacodynamic Effects Of (R)-mtd and (S)-mtd At ...mentioning
confidence: 99%